The role of media exposure on relational aggression: A meta-analysis. (July 2019) - Martins, Nicole; Weaver, Andrew
Abstract: We conducted a meta-analysis of 33 studies that examined the effects of media exposure on relationally aggressive behaviors and cognitions (a total of 66 effect sizes, N = (20, 990). Across all types of aggressive content, there was a small positive effect ( r = 0.15) on relational aggression. However, a comparison of effects sizes demonstrate that exposure to relational aggression had the strongest effect ( r = 0.21), whereas exposure to non-specific media content had the weakest effect ( r = 0.08). Exposure to physical aggression fell in the middle of the two content types ( r = 0.15). Potential explanations for these effects as well as moderators that could influence the results are considered, and the practical implications of these findings are discussed. Highlights: Exposure to relational aggression has the strongest effect on subsequent relational aggression Exposure to non-specific media content has the weakest effect on relational aggression Exposure to physical aggression fell in the middle of the two content types; supports cross-over effect Future research should study these issues among heterogeneous populations so moderating variables can be further examined.